Drug utilization study in outpatient ophthalmology department of government medical college, Nellore, India - Gorantla, Naveen Choudary; Hanumanthu, Lalitha (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drug utilization studies are an important part of rational use of drugs. This study was planned to assess drug utilization pattern in Ophthalmology outpatient department. Methods: After approval from Ethics Committee, 620 prescriptions were analyzed according to WHO drug indicators. Results: 2. 4 drugs were prescribed on an average per prescription. Antibiotics (49%) were the most commonly used drugs. Fluoroquinolones (54%) were frequently used. Topical route was preferred route of drug administration. Prescription of generic drugs was not optimal (13%). Duration of therapy was missing in many prescriptions. Conclusions: Generic prescribing can be improved. Duration of therapy should be mentioned in all prescriptions.